2008
DOI: 10.1080/07357900701708393
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Cohort Study of Dose-Dense Temozolomide (21 of 28 Days) for the Treatment of Recurrent Anaplastic Astrocytoma or Oligoastrocytoma

Abstract: Dose-dense temozolomide schedules deplete O6-methylguanine methyltransferase and may overcome chemoresistance. This multicenter cohort study enrolled 19 patients (15 anaplastic astrocytoma, 4 anaplastic oligoastrocytoma) who received temozolomide (100 mg/m2/day for 21 consecutive days every 28-day cycle) at first recurrence, either until disease progression or 12 cycles. Six-month progression-free survival was 56%, comparing favorably with historic controls treated with the standard 5-day temozolomide schedule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 21 publications
2
33
0
Order By: Relevance
“…Notably, long-term responses of 15 and 19 months were even achieved in patients with unmethylated MGMT promoter, pointing towards the efficacy of this MGMT-depleting strategy. The long-term response of all patients with grade III tumors indicates that the regimen is also effective in patients with anaplastic gliomas, an observation that supports recentlypublished promising results (13). Also of note is that objective responses and a favorable long-term outcome were observed even though, in a considerable number of patients, the regimen was switched, directly or within less than 3 months, from the conventional 5/28-day to the dose-dense 21/28-day regimen.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Notably, long-term responses of 15 and 19 months were even achieved in patients with unmethylated MGMT promoter, pointing towards the efficacy of this MGMT-depleting strategy. The long-term response of all patients with grade III tumors indicates that the regimen is also effective in patients with anaplastic gliomas, an observation that supports recentlypublished promising results (13). Also of note is that objective responses and a favorable long-term outcome were observed even though, in a considerable number of patients, the regimen was switched, directly or within less than 3 months, from the conventional 5/28-day to the dose-dense 21/28-day regimen.…”
Section: Discussionsupporting
confidence: 69%
“…Tosoni et al reported a considerable rate of pneumonia during a 21/28-day regimen for relapsed malignant glioma (14). However, a similar rate of infection was not observed by Neyns et al (13), who treated patients using the same regimen. In our series, 1 patient developed severe pneumonia 3 weeks after permanent discontinuation of chemotherapy for progression, without isolation of Pneumocystis carinii.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…[67][68][69][70][71][72][73][74] One particularly relevant question is whether concomitant RT plus temozolomide is sufficient to confer a survival benefit in patients with newly diagnosed GBM. This question is the object of an ongoing international Intergroup trial designed to establish the optimal sequence and relative contribution of the concomitant and adjuvant chemotherapy compared with RT alone in patients with anaplastic astrocytoma.…”
Section: Brain Tumor Trials With Novel Schedules Of Temozolomidementioning
confidence: 99%
“…The MGMT promoter methylation status was not associated with a difference in survival [9]. Profound lymphopenia was also reported in another trial looking at this treatment schedule, with a dose of 100 mg/m 2 , in the setting of recurrent disease [10]. A phase II trial of 90 patients with recurrent gliomas using the dose-dense schedule was feasible and safe and showed similar activity in patients with and without MGMT gene promoter methylation [11].…”
Section: Tmz Dose and Schedulementioning
confidence: 92%